Stages and changing Modus Operandi of Anglophone Separatists in Cameroon since 1984 - Nfi, Joseph Lon (Africana Studia, 2021)
The paper probes into the phases, strategies, tactics, operational methods and weapons used by Anglophone extremists to achieve their objective, the separation from the Republic of Cameroon. Since the reunification of Southern Cameroons and the Republic of Cameroon in 1961, the Anglophones of Southern Cameroons complained of marginalisation, neglect, exploitation, assimilation and domination by the Francophone dominated governments. While the moderate Anglophones are asking for genuine decentralisation or federalism, the extremists want outright secession. Based on primary and secondary sources and on my observations, it is argued that starting in 1984 when the president of Cameroon Paul Biya changed the name of Cameroon from the United Republic of Cameroon to the Republic of Cameroon, Anglophone extremists struggle for autonomy and/or secession of Southern Cameroon or Ambazonia became more radical, violent and bloody. It is likely that this violence and extremism will continue until a solution is provided to Africa’s latest secession war. Keywords: Ambazonia, Anglophone, Cameroon, Secession.